Genomic characterization of a unique Panton–Valentine leucocidin-positive community-associated methicillin-resistant Staphylococcus aureus lineage increasingly impacting on Australian indigenous communities - Ramsay, Joshua; Parahitiyawa, Nipuna; Mowlaboccus, S.; Mullally, C.A.; Yee, N.W.T.; Shoby, P.; Colombi, Elena; Tan, H.L.; Pearson, J.C.; Coombs, G.W. (2023)
In 2010 a single isolate of a trimethoprim-resistant multilocus sequence type 5, Panton–Valentine leucocidin-positive, community-associated methicillin-resistant Staphylococcus aureus (PVL-positive ST5 CA-MRSA), colloquially named WA121, was identified in northern Western Australia (WA). WA121 now accounts for ~14 % of all WA MRSA infections. To gain an understanding of the genetic composition and phylogenomic structure of WA121 isolates we sequenced the genomes of 155 WA121 isolates collected 2010–2021 and present a detailed genomic description. WA121 was revealed to be a single clonally expanding lineage clearly distinct from sequenced ST5 strains reported outside Australia. WA121 strains were typified by the presence of the distinct PVL phage φSa2wa-st5, the recently described methicillin resistance element SCCmecIVo carrying the trimethoprim resistance (dfrG) transposon Tn4791, the novel β-lactamase transposon Tn7702 and the epidermal cell differentiation inhibitor (EDIN-A) plasmid p2010-15611-2. We present evidence that SCCmecIVo together with Tn4791 has horizontally transferred to Staphylococcus argenteus and evidence of intragenomic movement of both Tn4791 and Tn7702. We experimentally demonstrate that p2010-15611-2 is capable of horizontal transfer by conjugative mobilization from one of several WA121 isolates also har-bouring a pWBG749-like conjugative plasmid. In summary, WA121 is a distinct and clonally expanding Australian PVL-positive CA-MRSA lineage that is increasingly responsible for infections in indigenous communities in northern and western Australia. WA121 harbours a unique complement of mobile genetic elements and is capable of transferring antimicrobial resistance and virulence determinants to other staphylococci.